Republic of Croatia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix examines the revenue and expenditure trends of the Croatia from a cross-country perspective and illustrates the medium-term fiscal outlook under two scenarios: one assumes gradual fiscal adjustment and structural reforms; the other assumes stronger fiscal adjustment and a more aggressive approach to structural reforms. The paper analyzes Croatia's revenue structure to provide a perspective for the medium-term revenue policy. It also identifies the expenditure items that could be streamlined over the medium term, and presents alternative medium-term fiscal frameworks.